Modulation of magnetic anisotropy and spin–orbit interaction by electrical current in FeCoB nanomagnets - Vadym Zayets (AIP Advances)
We present a novel method for measuring the modulation of magnetic anisotropy and the strength of spin–orbit interaction by an electrical current in nanomagnets. Our systematic study explores the current dependencies of these properties across a variety of nanomagnets with different structures, compositions, and sizes, providing unprecedented insights into the complex physical origins of this effect. We identified two distinct contributions to the observed current modulation: one proportional to the current and the other to the square of the current. The squared-current contribution, originating from the spin Hall effect, uniquely accumulates the strength with an increasing number of interfaces, resulting in exceptionally large current modulation of magnetic anisotropy and spin–orbit interaction in multilayer nanomagnets. Conversely, the linear-current contribution stems from the ordinary and anomalous Hall effects and exhibits opposite polarity at different interfaces, making it significant only in asymmetrical single-layer nanomagnets. The squared-current contribution induces substantial anisotropy field changes, up to 30%–50% at typical magnetic random access memory (MRAM) recording currents, leading to thermally activated magnetization reversal and data recording. The linear-current contribution, while smaller, is effective for parametric magnetization reversal, providing sufficient modulation for efficient data recording through resonance mechanisms. This finding highlights the complex nature of spin accumulation and spin dynamics at the nanoscale, presenting an opportunity for further optimization of data recording in MRAM technology.